Implementation of Police Chief’s Telegram Mail Number ST/2264/X/HUM.3.4.5/2022 About Law Enforcement for Violation of The Traffic Law an Empirical Study at The Traffic Control Center of State Police of DIY - Wasiati, Cunduk; Muhamad Ibnu Aldira Razak (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
The issuance of the circular letter of the Chief of Police Number: ST / 2264 / X / HUM.3.4.5 / 2022 dated October 18, 2022 affects the enforcement of traffic laws through ETLE. This is because the circular letter of the Chief of Police does not allow police members to do manual ticketing to violators even though there are only 4 types of violations through ETLE. Other violations should not be done manually. This research is classified as a type of descriptive research that has the characteristic data in the form of words and images. Descriptive research is research directed at describing symptoms, facts, or events in a special and accurate manner regarding the properties of a particular population or area. The method used in this study is a qualitative research method. Implementation of the Police Chief's Telegram Letter Number: ST/2264/X/HUM.3.4.5/2022 dated October 18, 2022 against law enforcement of traffic violations. In ditlantas Polda DIY, if it is implemented in order to carry out law enforcement for traffic offenders, it is still difficult to implement. This is because E-Tilang Sanctions can only be applied to 10 (ten) types of traffic violations, even though there are types of violations that are not included in that type, namely the obligation to have and carry a driving completeness letter in the form of a driver's license and STNK that cannot be detected by ETLE. Efforts to bring order to motorists who do not yet have a driver's license cannot be made. Likewise, efforts to reduce the crime rate in the form of motor vehicle theft due to the absence of stnk are also difficult to do. Factors inhibiting the implementation of the Police Chief's Telegram Letter Number: ST / 2264 / X / HUM.3.4.5 / 2022 dated October 18, 2022 against law enforcement of traffic violations in the Ditlantas Polda DIY are: Cultural and community factors, Factors of facilities and facilities, Factors of law enforcement apparat, Legal factor. Keywords:I mplementation, Telegram Letter, Chief of Police, ETLE